CURRENT ASPECTS OF FORMATION IN STUDENTS HEALTHY LIFESTYLE - Trofanova, T.H. (Pedagogy of Higher and Secondary Education, 2022)
In the article look at actual aspects increase level of health for children and have owning habits and skill of health life.